GRAPE’S LEATHER AND SEED EXTRACT (VITIS VINIFERA) IMPROVING THE FUNCTION OF WISTAR RATS’ MOTOR (RATTUS NORVEGICUS) ISCHEMIC STROKE MODEL - Indra, Muhamad Rasjad; Lie, Zanella Yolanda (Malang Neurology Journal, 2017)
Background. Grape peel and seed extract (Vitis vinifera), that has resveratrol, is one of many antioxidants that can pass through blood brain barrier and can induce release neurotrophic factor that contribute in ERK 1/2 pathway mechanism in post stroke.Objective. To prove that grape peel and seed extract can regenerate neuron in brain functional.Methods. True experimental design with five groups in this research. The five groups are negative control, positive control, grape peel and seed extract 50mg/KgBW, 100mg/KgBW, and 200mg/KgBW. rats are given grape peel and seed extract in variable dose to know how extract’s effect in neuron repairment. The repairment is monitored from ladder rung walking test score.Results. Range average score ladder rung walking test post stroke dan post treatment group N, K, Ra, Rb, dan Rc, were 0 ± 0, 0.001028933 ± 0.011664445, 0.123214286 ± 0.019834983, 0.064744427 ± 0.024296721, 0.03781401 ± 0.006888803. Statistical test used Annova significantly p;0,001.Dose 50mg/KgBW is effective in repairing neuron.Conclusion. Grape’s leather and Seed extract 50 mg/kgBW can improve neuron regeneration on animal model.